To Study the Occupational Stress and Job Satisfaction Experienced By School Teachers: Exploring the Link between Workplace Stress and Job Satisfaction among School Teachers (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The research can help to examine the connection between workplace stress and job satisfaction. This research will help to learn the degree of stress and work satisfaction of school teachers and the analysis findings will also help to explain the behavior of school teachers and private schools.Teaching is not an straightforward task as it is a dynamic process involving the willingness of teachers to communicate with pupils, their performance in school-related jobs, gaining value in information and the ability to establish a cordial relationship with their colleagues. The entire cycle of instruction, learning and interaction rests on the willingness of a instructor to be embraced without delay, who transforms a child's apparent potentialities into actuality. The method of teaching and learning cannot be performed in isolation, but it is a positive-directed practice for which teachers must be provided with teaching skills. The teacher is the main individual and the progress of the education system depends solely on the competence and skill of the teachers who are important in society.